2022
DOI: 10.3389/feduc.2022.1055722
|View full text |Cite
|
Sign up to set email alerts
|

Resourcefulness, narratives, and identity in science, technology, engineering, arts and mathematics education: A perspective of makerspaces for rural communities in Colombia

Abstract: Disparities of scientific education (STEM) in rural and remote communities are exacerbating inequalities and taking away opportunities for youth to explore their scientific interests and participate in science-making globally. Maker education in rural and remote areas of Latin America could boost the participation of rural communities in scientific education and open alternatives to the lack of higher literacy rates and STEM education. In Colombia, tertiary education has been making efforts to close this gap t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Indeed, the maker movement provides students with new paths for thinking and diverse ways to act, which is beneficial for cultivating their computational thinking (Resnick and Silverman, 2003;Blikstein, 2008). Recent studies indicated that creating a makerspace in which students learn in an enriched environment that emphasizes engagement, communication, practice, and innovation is beneficial for promoting students' maker spirit and competence Oswald and Zhao, 2021;Avendano-Uribe et al, 2022;Hughes et al, 2023;Leskinen et al, 2023). In addition, it is valuable to support and motivate students' learning autonomy (Ryan and Deci, 2000;Barron, 2006;Azevedo, 2011); that is, anyone can learn the skills they require to accomplish what they imagine (Dweck, 2000).…”
Section: Developing Students' Maker Competence For Future Interdiscip...mentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, the maker movement provides students with new paths for thinking and diverse ways to act, which is beneficial for cultivating their computational thinking (Resnick and Silverman, 2003;Blikstein, 2008). Recent studies indicated that creating a makerspace in which students learn in an enriched environment that emphasizes engagement, communication, practice, and innovation is beneficial for promoting students' maker spirit and competence Oswald and Zhao, 2021;Avendano-Uribe et al, 2022;Hughes et al, 2023;Leskinen et al, 2023). In addition, it is valuable to support and motivate students' learning autonomy (Ryan and Deci, 2000;Barron, 2006;Azevedo, 2011); that is, anyone can learn the skills they require to accomplish what they imagine (Dweck, 2000).…”
Section: Developing Students' Maker Competence For Future Interdiscip...mentioning
confidence: 99%
“…Previous research findings also indicated that STEAM education is valuable for promoting students' reflection on their own scientific reasoning (Bassachs et al, 2020), advancing their capabilities of oral communication (Botuzova, 2020), engaging them to actively work on targeted learning tasks effectively and innovatively (Lavrenova et al, 2020;Makonye, 2020), and providing all students with equal access to all fields of science, which can reduce the gender gap in science and technology (Guenaga Gómez and Fernández Álvarez, 2020;Kijima and Sun, 2020). Similarly, the maker movement, focusing on "hands-on, creation, design and innovation" (Peppler and Bender, 2013), shares this interdisciplinary nature and provides a creative learning environment for all students to think and act anew that is beneficial for nurturing their competencies (e.g., maker competence) Oswald and Zhao, 2021;Avendano-Uribe et al, 2022;Hughes et al, 2023;Leskinen et al, 2023). Hughes et al (2023) claimed that design thinking and collaboration are fundamental to developing the learning tasks of the maker curriculum.…”
Section: Interdisciplinary Nature Of Steam Education As the Foundatio...mentioning
confidence: 99%
See 2 more Smart Citations